Awareness on antibiotic usage among undergraduate medical students in a teaching hospital, Guntur - Mattam, Bheemesh Naidu; Prathyusha, D. L. N.; Yedurupaka, Santhi S.; Yerram, Sai V. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Antibiotics are the mainstay treatment of most of the infectious diseases. Inappropriate and irrational use of antimicrobial agents has led to increase in the development of antimicrobial resistance. Medical students are a part of health care system and they must be aware of increasing antibiotic resistance as they are the future prescribers. The objectives of the study were to assess the awareness on antibiotic usage and its resistance among medical students and to study the perception on antibiotic medication among medical students. Methods: This was a cross-sectional, semi-structured questionnaire-based study. Questionnaire consists of 4 parts- socio-demographic details, awareness on antibiotics and its resistance, knowledge on specific treatment of a disease, perception levels. Prior IEC approval was taken. The obtained data was statistically analyzed using Microsoft excel sheet. Results: Among 230 participants, majority of the students have awareness on general antibiotic usage and 97.8% were having knowledge about antibiotic resistance. The main source of information on antibiotic resistance is identified as classroom teaching (67.8%). 46.9% and 25.2% students correctly identified the drug of choice for treating enteric fever and community acquired pneumonia respectively. Conclusions: Degrees of awareness on antibiotics and its resistance is found to be good. Antibiotic usage pattern is not on par with knowledge. Knowledge on specific treatment of infectious disease is found to be less. So, antibiotic teaching should be integrated with clinical subjects.